ALTERNATIVE METHOD OF RGB CHANNEL SPECTROSCOPY USING A CCD READER - Gobato, Ricardo; Simões Filho, Manuel (Ciência e Natura, 2017)
Spectroscopy is a technique for collecting physicochemical data through the transmission, absorption or reflection of incident radiant energy in a sample. Our work is used in common low cost and easy access devices that have a CCD reader. Our idea is a set of devices, such as a cell phone, which contains an optical CCD reader, where these equipment materials, materials, compounds, simplifying the image obtained by these optical devices. As filming obtained by optical CCD reader theses hardware, form decoded and separated into their quantified RGB color channels. Our initial technique consists of the analysis of the pixels of the images of primary light sources, such as: the sun, incandescent lamps, fire, candle flames, matchestick flame, wood combustion, etc. We conclude that it is possible to do a spectroscopic analysis using our technique.